Perlindungan Hukum Terhadap Data Pribadi Konsumen Pada Pembelian Barang di Marketplace - Ida Bagus Wahyu Wira Kusuma; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2025)
Legal development in Indonesia focuses on regulation for the economy, particularly in e-commercee. While e-commerce facilitates transactions and affects the economy, cybercrime and personal data protection are threats. The problems are:  1. How is the regulation of consumer personal data on the purchase of goods in the marketplace? and 2. How is the legal protection of consumer personal data on the purchase of goods in the marketplace? This research uses normative research methods. The purpose of this study is to analyze the law in assisting legal protection of consumer personal data on the purchase of goods in the marketplace and analyze the challenges and obstacles faced by the law in handling cases of legal protection of consumer personal data on the purchase of goods in the marketplace. Privacy protection is regulated in the ITE Law and PP PSTE. Online legal remedies can be accessed to protect the privacy rights of ecommerce and Online marketplaces, following international legal mechanisms. Consumer rights in the Marketplace are regulated by Law No. 8 Year 1999 on Consumer Protection. MOCI Regulation No. 20/2016 supports consumer rights related to data protection and complaints. Electronic system operators, including marketplace companies, are required to establish internal rules, including privacy policies, to safeguard personal data.